Pengaruh Latihan Trun Shoot dan Redirct the Ball Terhadap Shooting Sepak Bola - Raden Suaka Arya Duta; Soemardiawan Soemardiawan; Ismail Marzuki (Jurnal Porkes, 2026)
Low shooting ability in young players is a major obstacle in scoring goals, especially when receiving the ball with back to goal. Initial observation of 20 Brilliant FC U-12 players showed shooting accuracy of only 38%, turn time of 2.8 seconds, and 72% of players lacked technique variations. This study aims to analyze the effect of turn shoot and redirect the ball drills on improving shooting ability of Brilliant FC U-12 players in 2026. This research used a quantitative approach with pre-test post-test control group design. The sample consisted of 20 players randomly divided into experimental group (n=10) given drills for 8 weeks (3x/week) and control group (n=10) undergoing regular training. The instrument used a shooting ability test measuring accuracy and shot speed. Results showed the experimental group's score increased from 65.4 ± 4.2 to 82.7 ± 5.1 (26.5%), while the control group increased from 64.8 ± 3.9 to 68.2 ± 4.3 (5.2%). The independent sample t-test showed significance of 0.001 (p < 0.05) with Cohen's d effect size of 1.82 (very large effect). In conclusion, turn shoot and redirect the ball drills have a significant effect on improving shooting ability of Brilliant FC U-12 players.